Groundwater‐River Water Exchange Enhances Growing Season Evapotranspiration and Carbon Uptake in a Semiarid Riparian Ecosystem. Issue 1 (12th January 2019) - Missik, Justine E. C.; Liu, Heping; Gao, Zhongming; Huang, Maoyi; Chen, Xingyuan; Arntzen, Evan; Mcfarland, Douglas P.; Ren, Huiying; Titzler, P. Scott; Thomle, Jonathan N.; Goldman, Amy
Abstract: Semiarid ecosystems play a critical role in determining the interannual variability of the global terrestrial carbon sink. Water availability is a critical driver of productivity in semiarid ecosystems, which often alternate between carbon sink/source functioning during wet/dry years. In this study, we investigate how groundwater availability resulting from groundwater‐river water exchange influences net ecosystem exchange of CO2 (NEE), evapotranspiration (ET), and the surface energy balance at two semiarid ecosystems along the Columbia River in central Washington, USA. We examined 1 year of eddy covariance measurements from an upland sagebrush ecosystem primarily fed by rainfall without groundwater access and a riparian grassland ecosystem with groundwater access during the dry season due to lateral groundwater‐river water exchange. The two sites had distinct seasonal patterns of NEE and ET, driven by differences in water availability. While NEE at the upland sagebrush site was strongly constrained by water availability during the dry months, access to groundwater allowed the riparian site to maintain high NEE magnitude and ET during the same dry months. The riparian site had larger annual gross primary productivity than the upland site (612 vs. 424 gC/m 2 ), which was offset by higher ecosystem respiration (558 vs. 363 gC/m 2 ). Thus, the magnitude of the annual NEE at the upland site was larger than that at the riparian site (−62 vs. −54 gC/m 2 ). Our results demonstrate that groundwater access determined by connectivity between groundwater and surface water can be a critical driver of carbon uptake and ET in semiarid ecosystems. Plain Language Summary: Semiarid ecosystems play a critical role in determining the interannual variability of the global terrestrial carbon sink. Water availability is a critical factor influencing the productivity of semiarid ecosystems, which often alternate between functioning as carbon sinks during wet years and carbon sources during dry years. In this study, we investigate how groundwater availability resulting from groundwater‐river water exchange influences carbon uptake and evapotranspiration at two semiarid ecosystems along the Columbia River corridor in central Washington, USA. We examined 1 year of measurements from an upland sagebrush ecosystem without groundwater access and a riparian grassland ecosystem with access to groundwater during the dry season due to lateral groundwater‐river water exchange. The two sites had distinct seasonal patterns of carbon uptake, driven by differences in water availability between the two sites. While carbon uptake at the upland sagebrush site was strongly constrained by water availability during the dry summer months, access to groundwater allowed the riparian site to maintain high carbon uptake and evapotranspiration during the same dry months. Our results demonstrate that groundwater access can be a critical factor influencing carbon uptake and evapotranspiration in semiarid ecosystems. Key Points: The effects of water accessibility on carbon and water cycling in semiarid ecosystems are investigated Carbon uptake was strongly constrained by moisture availability during dry months in an upland ecosystem without groundwater access Lateral groundwater‐river water exchange allowed a riparian semiarid ecosystem to maintain high carbon uptake and evapotranspiration during dry months